2016
DOI: 10.1080/01616412.2015.1105627
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgery for ICH evacuation followed by rosiglitazone infusion therapy increased perihematomal PPARγ expression and improved neurological outcomes in rabbits

Abstract: Performing MIS followed by PPARγ agonist infusion therapy is more efficacious for reducing secondary damage to the brain and improving neurological function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…NF-kB activation is regulated by the PPAR transcription factors (Deng et al, 2016). PPARγ, the most studied PPAR isoform, has shown the most potent neuroprotective effects in different models of neurodegenerative disorders such as I/R-induced brain injury and AD (Zhao et al, 2006; Zolezzi et al, 2014; Wu et al, 2016; Chen et al, 2018). Consistent with this, co-treatment of the MCAO rats with 1, 25-D 3 and a PPARγ inhibitor blocked the protective effects of the former, on brain injury (Grommes et al, 2013; Wang et al, 2016; Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…NF-kB activation is regulated by the PPAR transcription factors (Deng et al, 2016). PPARγ, the most studied PPAR isoform, has shown the most potent neuroprotective effects in different models of neurodegenerative disorders such as I/R-induced brain injury and AD (Zhao et al, 2006; Zolezzi et al, 2014; Wu et al, 2016; Chen et al, 2018). Consistent with this, co-treatment of the MCAO rats with 1, 25-D 3 and a PPARγ inhibitor blocked the protective effects of the former, on brain injury (Grommes et al, 2013; Wang et al, 2016; Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that the use of rosiglitazone can relieve secondary brain injury [8][9]. Although the mechanism is still unclear, it has been shown that rosiglitazone acts as a specific agonist of PPARγ and regulates downstream genes through multiple signaling pathways, such as the pathways of PPARγ, Ras-Raf-MAPK, Transforming Growth Factor (TGF), and β-Catenin.…”
Section: Introductionmentioning
confidence: 94%
“…Clinical evidence shows that hematoma size and expansion are the major determinants of ICH outcomes (Brott et al, 1997; LoPresti et al, 2014). Until now, however, little preclinical work has evaluated potential strategies to limit hematoma expansion or accelerate hematoma resolution after ICH (Flores et al, 2016; King et al, 2011; Wu et al, 2016; Zhao et al, 2015b; Zhao et al, 2007b). …”
Section: Introductionmentioning
confidence: 99%